A Characterization of Compact SG Pseudo-differential Operators on L2(ℝn). (17th July 2014) - Molahajloo, S.
Abstract : We give a necessary and sufficient condition for pseudo-differential operators with SG symbols to be compact from L 2 ( ℝ n ) into L 2 ( ℝ n ).